IMPLEMENTATION OF CHARACTER EDUCATION PROGRAM IN VOCATIONAL SCHOOL, LEBONG DISTRICT - Sumarsih, Sumarsih; Zakaria, Zakaria (Universitas Ahmad Dahlan, 2020)
The purpose of the research is to describe the implementation of strengthening character education at the Vocational High School in Bengkulu. This research is a quantitative descriptive study. The study population was 156 students, and the study sample used a random sampling sample of 75 students. Data collection techniques using a questionnaire. Data analysis techniques using percentage analysis. The results showed the application of strengthening of character educationÂ Vocational High Schools in Bengkulu; in general, the level has implemented with functional categories with a level of accomplishment reaching 75.4%. Specifically, the religious character value is good (78%), the nationalist is good (74%), independent is good (72%), cooperation is good (77%), and integrity is good (76%). It means that the strengthening of character education consists of religious, nationalist, independent, cooperation, and integrity values carried out by teachers and students according to school programs